Measure of fracture toughness of compressive fiber failure in composite structures using infrared thermography. (20th May 2015) - Lisle, Teddy; Bouvet, Christophe; Hongkarnjanakul, Natthawat; Pastor, Marie-Laetitia; Rivallant, Samuel; Margueres, Philippe
Abstract: Fracture toughness is one of the most important properties of any material for a lot of design applications involving damage and crack growth. Unfortunately, its value can be difficult to evaluate with standard methods such as the "compliance" method. In this work, two special cases have been studied and infrared thermography has been used to overcome the limitations of conventional methods. Compressive fiber failure in unidirectional composite laminate has been chosen due to its difficulty to evaluate toughness. Infrared thermography has been employed to follow compressive failure mode developing during an indentation test and a compression after impact test, and to evaluate the fracture toughness of compressive fiber failure. The obtained results show a good correspondence with the value found in a previous work on FE analysis of impact damage and are consistent with the literature.